‘Rapport myopia’ in investigative interviews: Evidence from linguistic and subjective indicators of rapport - Richardson, Beth H. (Legal and criminological psychology, 2022)
Purpose Rapport-building has beneficial effects in investigative and security contexts. However, there remains limited understanding of the extent of agreement between different parties in their judgments of rapport. Methods We observed 133 mock suspect interviews, and subsequently surveyed the lead interviewer and secondary interviewer (trainees undertaking an undergraduate Policing programme), the ‘suspect’ (an actor), and an expert observer (a retired, highly experienced police detective). Each of these parties provided subjective judgments of the degree of rapport that had been formed between suspect and lead interviewer. Furthermore, we assessed whether these subjective judgments were associated with the degree of ‘Language Style Matching’ (LSM) between lead interviewer and suspect: a key linguistic measure of interpersonal synchrony. Results The suspect, secondary interviewer, and expert observer had generally good agreement about the degree of rapport achieved, as evidenced through significant, moderate to strong correlations between their rapport ratings. However, these parties’ rapport ratings were weakly associated with those of the lead interviewer. Our linguistic analysis provided similar results: the extent of LSM was significantly associated with suspects’ and the expert’s subjective ratings of rapport, but not with the interviewers’ ratings. Conclusions The findings suggest that the demands of interviewing might impede interviewers’ insight into the success of their rapport-building efforts, leading them to overlook cues that other parties rely upon. We discuss the need for future experimental manipulations to directly test this suggestion, and we consider the value of interpersonal synchrony in defining and measuring rapport.